P7C3 Inhibits LPS-Induced Microglial Activation to Protect Dopaminergic Neurons Against Inflammatory Factor-Induced Cell Death in vitro and in vivo - Gu, Chao; Hu, Qingsong; Wu, Jiayuan; Mu, Chenchen; Ren, Haigang; Liu, Chun-Feng; Wang, Guanghui (Frontiers in Cellular Neuroscience, 2018)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder. Although its pathogenesis remains unclear, growing evidencce suggests that microglia-mediated neuroinflammation contributes greatly to the progression of PD. P7C3, an aminopropyl carbazole, possesses significant neuroprotective effects in several neurodegenerative disease animal models, including PD. In this study, we designed to investigate the effects of P7C3 on neuroinflammation. We showed that P7C3 specially suppressed the expression of lipopolysaccharide (LPS)-induced pro-inflammatory factors but not influenced the anti-inflammatory factors in microglia. The inhibition of the nuclear factor κB (NF-κB) signaling pathway was involved in the mechanisms of the anti-inflammatory effects by P7C3. LPS-induced activation of IκB kinase (IKK), degradation of the inhibitory κB alpha (IκBα) and nuclear translocation of NF-κB can be attenuated by the pretreatment of P7C3 in microglia. Furthermore, in LPS-treated microglia, P7C3-pretreatment decreased the toxicity of conditioned media to MES23.5 cells (a dopaminergic cell line). Most importantly, the anti-inflammatory effects of P7C3 were observed in LPS-stimulated mouse model. In general, our study demonstrates that P7C3 inhibits LPS-induced microglial activation through repressing the NF-κB pathway both in vivo and in vitro, providing a theoretical basis for P7C3 in anti-inflammation.